Efektivitas Komunikasi Pemasaran Iklan Head And Shoulders Di Youtube Terhadap Keputusan Membeli Mahasiswa Ilmu Komunikasi Universitas Tidar - Purnama Sani Wulandani; Fadilla Khairun Nisa; Naila Jannati A (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
In the digital era, social media has become a trend in the marketing world. Social media is online media where users can contribute, share and create content. Social media is used for business or to help market products/services, communicate with buyers and suppliers, reduce costs, and for online sales. Online marketing or online marketing communication is a strategy to use the internet that can be reached by audiences. This study aims to find out whether Head & Shoulders Ads can attract and even influence purchasing decisions for Tidar University Communication Studies students to buy the product or not. The type of research used in this study is descriptive quantitative, namely by collecting data using survey methods, namely using a questionnaire to obtain data and information that is considered as a sample that can represent the entire population.